The Receptor-like Kinase TaCRK-7A Inhibits Fusarium pseudograminearum Growth and Mediates Resistance to Fusarium Crown Rot in Wheat - Tianci Wu (MDPI AG, 2021)
The fungus F. pseudograminearum can cause the destructive disease Fusarium crown rot (FCR) of wheat, an important staple crop. Functional roles of FCR resistance genes in wheat are largely unknown. In the current research, we characterized the antifungal activity and positive-regulatory function of the cysteine-rich repeat receptor-like kinase TaCRK-7A in the defense against F. pseudograminearum in wheat. Antifungal assays showed that the purified TaCRK-7A protein inhibited the growth of F. pseudograminearum. TaCRK-7A transcript abundance was elevated after F. pseudograminearum attack and was positively related to FCR-resistance levels of wheat cultivars. Intriguingly, knocking down of TaCRK-7A transcript increased susceptibility of wheat to FCR and decreased transcript levels of defense-marker genes in wheat. Furthermore, the transcript abundances of TaCRK-7A and its modulated-defense genes were responsive to exogenous jasmonate treatment. Taken together, these results suggest that TaCRK-7A can directly inhibit F. pseudograminearum growth and mediates FCR-resistance by promoting the expression of wheat defense genes in the jasmonate pathway. Thus, TaCRK-7A is a potential gene resource in FCR-resistant wheat breeding program.